KOMPARASI METODE FORMULASI INTENSITAS HUJANANTARA KAWASAN DAERAH ALIRAN SUNGAI (DAS) SEMITAN DANDAERAH ALIRAN SUNGAI (DAS) SEBERANG (RANAI, KABUPATEN NATUNA) - Delvia, Magdalena; Nirmala, Azwa; Chatib, Nashrullah (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
The rainfall station distance which is located not far apart will produce the same formulation rain intensity. The formulation that are commonly known to calculate the rainfall intensity is the Talbot formulation, Sherman formulation dan ishiguro formulation. The aim of this research is to know whether both of the watershed have the same or different formulation method. This research was conducted in Ranai City, Natuna. The result shows that of watershed Semitan has the smallest value of standard deviation that in 23,747 with Sherman formulation methods and the correlation value is 0,9997 whereas the Seberang of watershed has the smallest value of standard deviation that is 22,206 with Sherman formulation methods and the correlation value is 0,9996. keywords : Rainfall Intensity, Ranai, Sherman, River